Detection and Occurrence of Indicator Organisms and Pathogens. (1st October 2013) - Kronlein, Maggie R.; Stedtfeld, Robert D.; Sorensen, Jackson; Bhaduri, Prianca; Stedtfeld, Tiffany; Eanes, Samantha; Harichandran, Vikram; Haynes, Kathleen; Stevens, Michael; Hashsham, Syed A.
Abstract : This review summarizes the literature published in 2012 pertaining to the occurrence and detection of fecal indicator bacteria (FIB) and pathogens. It is organized into the following sections: i) methods for the detection and quantification of waterborne fecal indicators and pathogens including polymerase chain reaction (PCR), isothermal amplification, label‐free methods, microarrays, immunoassay‐based methods, microfluidic‐based methods, and advances in sample processing and concentration at the limit of detection (LOD), ii) microbial source tracking (MST) using both genotypic and phenotypic‐based methods, iii) environmental occurrence, persistence, and transport of fecal indicators and pathogens.